Literature Review: The Effectiveness of Recell in Wound Healing Burn - Reeny Purnamasari; Selin Iriana Pasombak; Solecha Setiawati; Berry Erida Hasbi (Sean Institute, 2025)
Background: Burns are serious tissue injuries that require rapid treatment to prevent infection, accelerate healing, and reduce the risk of scarring. One therapeutic innovation is Autologous Skin Cell Suspension (ASCS) using the ReCell device. Based on a real-world registry data study from the United States (Burn Care Quality), ReCell uses a small sample of patient skin processed into a cell suspension and sprayed onto the wound to stimulate skin regeneration and improve healing outcomes. Objective: This literature review aims to analyze the effectiveness of ReCell in healing burns based on ten articles published in the period 2018–2025. Methods: The literature review was obtained from PubMed, ScienceDirect, and Google Scholar, then analyzed narratively. Results: The study results showed that ReCell accelerates re-epithelialization with a shorter healing time compared to conventional skin grafts, and reduces the need for a skin donor area by more than 30%. In addition, ReCell provides better aesthetic results, although its effectiveness in reducing pain, infection, and repigmentation has not been consistent. Several pediatric studies also reported the success of ReCell as a monotherapy. Conclusion: ReCell is a promising method to help heal second-degree (deep partial thickness) to third-degree (full thickness) burns.